Nourished: How Africa can build a future free from hunger and malnutrition - Malabo Montpellier Panel; Hendriks, Sheryl L.; Arnold, Tom; Conway, Gordon; Caron, Patrick; Nkombo, Nachilala; Tumusiime, Rhoda Peace; Glatzel, Katrin; Tankari, Mahamadou Roufahi (International Food Policy Research Institute, 2017)
The main objective of this report is to identify interventions that work and recommend options for policies and programs to eliminate hunger and malnutrition in all its forms. The report begins with a review of the African and global policy agenda, setting out the challenges and complexity of addressing all forms of malnutrition in Africa. It then offers an overview of successful interventions and innovative approaches that have been implemented in some countries and discusses critical threats—climate change and conflicts—that jeopardize progress on reducing malnutrition. Lastly, the report reviews the experiences of seven African countries that have been particularly successful in reducing malnutrition levels and draws some important lessons for other countries.